2010
DOI: 10.1007/s12640-010-9236-5
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Neuronal Activation by Alpha2A Adrenergic Receptor Agonist

Abstract: Stress factors induce neuronal activation in brain areas that are related to anxiety and fear. High doses of caffeine induce neuronal activation with Ca2+ influx followed by expression of the immediate early gene c-fos. In the present study, we investigated c-Fos protein expression in stress-responsive brain areas induced by caffeine, as well as the role of alpha2A receptor in the regulation of neuronal activation. Immunohistochemical analysis showed that an acute effect of caffeine induced c-Fos protein expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Increased expression of Ntng2 as observed in our WTs after acute stress in turn therefore might reflect the preparation of the organism to an increased startle response after an acute stressor which resembles a sensitization or increased arousal or fear. A comparable conclusion can be drawn for Adra2a that modulates synaptic transmission via inactivation of adenyl cyclase and decrease of cAMP in response to catecholamines in neuronal circuits that are correlated with stress in vivo [49]. A rapid downregulation as observed in our stressed WTs probably reduces these inhibitory effects, resulting in an enhanced neurotransmitter release and therefore a more vigorous arousal or fear and stress reaction.…”
Section: Discussionsupporting
confidence: 81%
“…Increased expression of Ntng2 as observed in our WTs after acute stress in turn therefore might reflect the preparation of the organism to an increased startle response after an acute stressor which resembles a sensitization or increased arousal or fear. A comparable conclusion can be drawn for Adra2a that modulates synaptic transmission via inactivation of adenyl cyclase and decrease of cAMP in response to catecholamines in neuronal circuits that are correlated with stress in vivo [49]. A rapid downregulation as observed in our stressed WTs probably reduces these inhibitory effects, resulting in an enhanced neurotransmitter release and therefore a more vigorous arousal or fear and stress reaction.…”
Section: Discussionsupporting
confidence: 81%
“…The CeA has a well‐established role in stress‐induced behaviors, and the CeL but not the CeM mediates relapse to methamphetamine self‐administration . Guanfacine increased CeL Arc immunoreactivity (Figure C,D), as seen previously, but nicotine‐treated groups showed decreased CeL activity overall. Previous studies have shown enhanced c‐fos immunoreactivity in the CeA after incubation of nicotine self‐administration and after footshock which followed nicotine self‐administration training .…”
Section: Discussionmentioning
confidence: 94%
“…Antigen expression, including c-Fos, was assessed using standard IHC procedures, with a rabbit polyclonal anti-c-Fos antibody (sc-52, Santa Cruz Biotechnology); M2-type muscarinic acetylcholine receptors were labeled using a rat monoclonal anti-M2 antibody (MAB 367, EMD Millipore). Primary antibody labeling was visualized with either fluorescent or non-fluorescent secondary antibodies (see our previous papers for detailed methods, (Savchenko and Boughter, 2011;Tokita and Boughter, 2016…”
Section: Methodsmentioning
confidence: 99%